2016
DOI: 10.1186/s12889-016-3287-3
|View full text |Cite|
|
Sign up to set email alerts
|

The effectiveness of non-pyrethroid insecticide-treated durable wall lining to control malaria in rural Tanzania: study protocol for a two-armed cluster randomized trial

Abstract: BackgroundDespite considerable reductions in malaria achieved by scaling-up long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS), maintaining sustained community protection remains operationally challenging. Increasing insecticide resistance also threatens to jeopardize the future of both strategies. Non-pyrethroid insecticide­treated wall lining (ITWL) may represent an alternate or complementary control method and a potential tool to manage insecticide resistance. To date no study has dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 50 publications
0
38
0
8
Order By: Relevance
“…Although Cochrane reviews remain the gold standard in evidence-based policy, it is often inappropriate to combine findings from studies across different eco-epidemiological settings when VCT efficacy is tied to local transmission ecology (Walshe et al, 2013;Tusting et al, 2013). Second, some emerging VCTs remain years away from accumulating a full dossier of epidemiological evidence, and although further Phase III studies are planned (Thomas M et al, 2015), nearing completion (Mtove et al, 2016), or recently concluded (Homan et al, 2017), we identified fourteen VCTs for which no Phase III epidemiological data were available within the search dates. Demonstrating protection against disease and/or infection is critical before any VCTs can be recommended for large-scale deployment (Wilson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although Cochrane reviews remain the gold standard in evidence-based policy, it is often inappropriate to combine findings from studies across different eco-epidemiological settings when VCT efficacy is tied to local transmission ecology (Walshe et al, 2013;Tusting et al, 2013). Second, some emerging VCTs remain years away from accumulating a full dossier of epidemiological evidence, and although further Phase III studies are planned (Thomas M et al, 2015), nearing completion (Mtove et al, 2016), or recently concluded (Homan et al, 2017), we identified fourteen VCTs for which no Phase III epidemiological data were available within the search dates. Demonstrating protection against disease and/or infection is critical before any VCTs can be recommended for large-scale deployment (Wilson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 18 clusters were selected; nine in control clusters and nine in intervention clusters from clusters in a randomized field trial [ 18 ]. Intervention clusters were those with high percentage (over 80%) coverage of durable wall liners installation and they were provided with LLINs while control clusters were the ones which were provided with LLINs alone.…”
Section: Main Textmentioning
confidence: 99%
“…Intervention clusters were those with high percentage (over 80%) coverage of durable wall liners installation and they were provided with LLINs while control clusters were the ones which were provided with LLINs alone. The core area of each cluster had a minimum of 124 households [ 18 ]. In each cluster, four houses with open eaves and unscreened windows were selected.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this published article [1] would like to correct the ‘Funding’ declarations to read as follows:…”
Section: Erratummentioning
confidence: 99%